Tahfidz Assessment Monitoring System and Website-Based Activities at Hamalatul Qur'an Islamic Boarding School Jogoroto Jombang - Ridhoi Asyari, Muhammad; Khafidhoh, Nur; Munawarah (Bahasa Indonesia, 2024)
A person who memorizes the Qur'an is guaranteed to enter heaven by Allah, as well as being the best among other people, because of this virtue, many believers flock to memorize the Qur'an. Likewise, the Hamalatul Qur'an Islamic Boarding School makes memorizing the Qur'an its flagship program. However, there are several shortcomings of the rote memorization system which is still manual, including memorization books which are often lost, students who do not make deposits are not known so they are not subject to sanctions and the students' guardians cannot monitor their sons' activities while they are at the Islamic boarding school. Given these problems, this research aims to develop a monitoring system for tahfidz assessment and santri activities. The research method used in this research is the Research and Development method with a waterfall development model with application testing using black-box, while data collection is through interviews, literature studies and field observations. The conclusion obtained from this research is that the monitoring system for tahfidz assessments and website-based activities in Islamic boarding schools is to help Islamic boarding school administrators manage memorization data and student activities and the guardians of Islamic boarding schools can monitor their sons who are in Islamic boarding schools.